Chardin’s Divine Milieu as Touchstone: Freedom, Creativity, and the Spiritually Centered Life in Brideshead Revisited - Melfi, Mary Ann (Religion and the arts, 2019)
Chardin wrote The Divine Milieu in 1927 (published in 1957). Waugh could not have known Chardin’s essay before the publication of Brideshead Revisited, but he demonstrates similar ideas concerning one’s spiritual development. A primary goal of both writers was to reconcile the apparent duality of matter and spirit. They argue for the necessity of individual freedom in one’s spiritual search, the value of creative work of all kinds in building spiritual insight, and the importance of perceiving divine influence at the center of all things.